A systematic review of treatment response rates in Pakistani hepatitis C virus patients; current prospects and future challenges. Issue 50 (December 2016) - Ali, Muhammad; Afzal, Samia; Zia, Asad; Hassan, Ahmed; Khalil, Ali Talha; Ovais, Muhammad; Shinwari, Zabta Khan; Idrees, Muhammad
Abstract: Background: The estimated hepatitis C virus (HCV) carriers are approximately 10 million in Pakistan which usually progresses to chronic hepatitis, with rare cases of spontaneous viral eradication. The present article reviews the treatment status of HCV infection in Pakistani population and various factors associated with the treatment response rates. Methods: Literature on anti-HCV therapy was searched in PubMed, Google Scholar and PakMediNet. Thirty three different studies representing different geographic regions of Pakistan published from 2002 to 2016 were included in the present review. Weighted mean, standard error estimates (SE) and standard deviation (SD) were determined for each population group. Results: Mean value for sustained virological response (SVR) for standard IFN plus ribavirin (RBV) combination therapy was 68.38% ± 14.13% (range 33.8%–87.10%; SE 3.08) and pegylated-IFN plus RBV combination therapy 64.38% ± 8.68% (range 55.0%–76.00%; SE 3.88). The lowest value for SVR has been reported to be 24.3% (for genotype 1; administering INF-α 2b 3MU 3 times/week and RBV 1000–1200 mg/day for 48 weeks) while highest of 87.5% (genotype 3a; INF-α 2a 3MU 3 times/week and RBV 1000–1200 mg/day for 24 weeks). The mean value for rapid virological response (RVR) was found to be 48.18% ± 29.20% (SE 9.73). As PEG-interferon and direct acting antivirals (DAAs) are relatively expensive, interferon-alfa (IFN-α) and RBV combination therapy have been used widely to treat HCV infected patients in Pakistan for the last one and half decade. On average, 2.45% of the patients discontinued treatment due to severe side effects. Conclusion: We encourage further studies on understanding host and viral factors associated with specific focus on harder to treat viral variants (relapsers and nonresponders). These variants are currently rising in the country.